Analysis of Conceptual Understanding in Matrix Operations among Grade XI Students of SMA Negeri 5 Palu Viewed from Learning Styles - Sakina Sakina; Dasa Ismaimuza; Bakri M Bakri M; Tegoeh S Karniman (Journal of Educational Sciences, 2026)
Conceptual understanding is an essential ability in mathematics learning, particularly in the topic of matrix operations, which requires accuracy and interconnection among concepts. This study aims to describe students’ mathematical conceptual understanding in solving matrix operations, viewed from visual, auditory, and kinesthetic learning styles. The research employed a descriptive qualitative approach with three Grade XI students, each representing one category of learning style. Data were collected through a conceptual understanding test on matrix operations and in-depth interviews, then analyzed through the stages of data condensation, data presentation, and conclusion drawing. The findings indicate that students with a visual learning style are able to understand concepts through table representations and the arrangement of matrix elements, yet still face difficulties in modeling word problems. Students with an auditory learning style can explain concepts orally in a structured manner, but show less consistency in calculation accuracy. Meanwhile, students with a kinesthetic learning style are able to grasp concepts through direct activities and modeling, and present solution steps systematically. The conclusion of this study highlights that differences in learning styles influence the characteristics of students’ mathematical conceptual understanding in solving matrix operations.